#### Answer

$\dfrac{3}{9x+6}=\dfrac{1}{3x+2}$

#### Work Step by Step

$\dfrac{3}{9x+6}$
Take out common factor $3$ in the denominator. Then, simplify:
$\dfrac{3}{9x+6}=\dfrac{3}{3(3x+2)}=\dfrac{1}{3x+2}$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$\dfrac{3}{9x+6}=\dfrac{1}{3x+2}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.